(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article study discussed the challenges of having an efficient database to address COVID-19 in the Malaysian context as a developing country. Likewise, the challenges include the management of the database system, which can share patient confidential information. It also implies good governance and strategy to enable an intelligent citizen-centred design that focuses on the usability and plan to benefit during post-COVID-19 with an efficient health information system in IR 4.0 era. The approach of this study is from content analysis of current literature, particularly during post-pandemic COVID-19. The listed factors are Shareable; Accessible Distributed Database; Data Protection; Backup Data Software Application Design and Development; Security and False News; and Systematic Integrated Monitoring System.Therefore, this article proposed criteria for a better health management system during the post-COVID-19 pandemic.